The invention of writing on Rapa Nui (Easter Island). New radiocarbon dates on the Rongorongo script - Ferrara, Silvia; Tassoni, Laura; Kromer, Bernd; Wacker, Lukas; Friedrich, Michael; Tonini, Francesca; Lastilla, Lorenzo; Ravanelli, Roberta; Talamo, Sahra (Scientific reports, 2024)
Placing the origin of an undeciphered script in time is crucial to understanding the invention of writing in human history. Rapa Nui, also known as Easter Island, developed a script, now engraved on fewer than 30 wooden objects, which is still undeciphered. Its origins are also obscure. Central to this issue is whether the script was invented before European travelers reached the island in the eighteenth century AD. Hence direct radiocarbon dating of the wood plays a fundamental role. Until now, only two tablets were directly dated, placing them in the nineteenth c. AD, which does not solve the question of independent invention. Here we radiocarbon-dated four Rongorongo tablets preserved in Rome, Italy. One specimen yielded a unique and secure mid-fifteenth c. date, while the others fall within the nineteenth c. AD. Our results suggest that the use of the script could be placed to a horizon that predates the arrival of external influence.